Studi Sosiolinguistik tentang Fatis dalam Film La Hila Donggo karya Ary Ipan - Adawiyah, Rabiyatul; Hasanah, Uswatun (Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to (1) describe the forms of language features in the film La Hila Donggo, and (2) explain the functions of language features in the film La Hila Donggo. This is a qualitative and descriptive study using a sociolinguistic approach. The data source for this study is the speech of characters in the film La Hila Donggo by Ary Ipan on the YouTube channel Medicana Studio. The research data consists of the speech of characters that describe the forms and functions of speech acts. The data collection technique used in this study is observation and note-taking. Furthermore, the data analysis technique uses the specific element sorting technique (PUP), where the data obtained will be grouped and analyzed based on the selected theory. The results of the study concluded that (1) four forms of fatis were found, namely fatis particles, fatis words, fatis phrases, and combined fatis forms, with 24 forms of fatis particles, 5 forms of fatis words, 4 forms of fatis phrases, and 3 forms of combined fatis. (2) The functions of fatis in the film La Hila donggo are broadly categorized as initiating, maintaining, emphasizing, inviting, confirming, and reinforcing the content of the conversation.